Total synthesis of the marine natural product solomonamide B necessitates stereochemical revision - Kashinath, K.; Jachak, Gorakhnath R.; Athawale, Paresh R.; Marelli, Udaya Kiran; Gonnade, Rajesh G.; Reddy, D. Srinivasa (Organic Letters, 2016)
The first total synthesis of the proposed structure of solomonamide B has been achieved. However, the H-1 and C-13 NMR spectral data of the synthesized compound was not exactly matching with that of the natural solomonamide B. This prompted us to revise the originally proposed structure, in particular, the stereochemistry of the nonpeptide part, which was confirmed by its total synthesis. During the course of the synthesis, we have developed an interesting hydroxy group directed Wacker oxidation of internal olefins in a macrocyclic setting.

Total synthesis, structure elucidation and expanded bioactivity of icosalide A: effect of lipophilicity and ester to amide substitution on its bioactivity - Dangi, Abha; Pande, Bharat; Agrawal, Sonia; Sarkar, Dhiman; Vamkudoth, Koteswara Rao; Marelli, Udaya Kiran (Organic & Biomolecular Chemistry, 2023)
The first total synthesis of icosalide A, an antibacterial depsipeptide that is unique in that it contains two lipophilic beta-hydroxy acids, has been achieved by following Fmoc solid-phase peptide synthesis in combination with solution-phase synthesis. The ambiguity in the absolute stereochemistry of icosalide A has been resolved by synthesizing the reported structures and other relevant diastereomers of icosalides and comparing their NMR data. NMR-based structure elucidation of icosalide A revealed a well-folded structure with cross-strand hydrogen bonds similar to the anti-parallel beta-sheet conformation in peptides and displayed a synergistic juxtaposition of the aliphatic sidechains. 12 analogues of icosalide A were synthesized by varying the constituent lipophilic beta-hydroxy acid residues, and their biological activities against Bacillus thuringiensis and Paenibacillus dendritiformis were explored. Most of these icosalide analogues showed an MIC of 12.5 & mu;g mL(-1) against both bacteria. Swarming inhibition by icosalides was least in B. thuringiensis (8.3%) compared to that in P. dendritiformis (33%). Furthermore, this is the first report of icosalides showing assured inhibitory action (MIC between 2 and 10 & mu;g mL(-1)) against the active stage of Mycobacterium tuberculosis and cancer cell lines such as HeLa and ThP1. This study could help optimize icosalides for anti-TB, antibacterial, and anti-cancer activities.